Assessment of Tear Film Anomalies in Childhood Obesity - Bayat, Alper Halil; Aydemir, Emre; Aydemir, Gozde Aksoy; Gencer, Hasim (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To determine if childhood obesity has an effect on the ocular surface and tear film of children who are afflicted.Methods Patients who had childhood obesity, 85 eyes, and patients who were healthy, 75 eyes, were enrolled in this prospective and comparative study. The tear film breakup time (TF-BUT), tear meniscus area and height (TMA and TMH) values, Schirmer test scores, and ocular surface disease index (OSDI) scores were obtained for all participants.Results The TMH, TMA, TF-BUT, and Schirmer test results were statistically significantly lower in the obesity group (p < 0.001 for all). The children with obesity and insulin resistance had lower TMH, TMA, TF-BUT, and Schirmer test results when compared to the children without insulin resistance (p < 0.05 for all). The body mass index was found to be correlated with the TMH, TMA, TF-BUT, and Schirmer test results (p < 0.001 for all).Conclusion Children with obesity had lower TMA, TMH, TF-BUT, and Schirmer test results than healthy subjects. When insulin resistance was added to obesity, these values were even lower.
Keywords: cornea; pediatric ophthalmology; conjunctiva